Byzantine music in the educational and scientific space of modern Ukraine - Ignatenko, Yevgeniya (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2023)
Relevance of the research. The persistent revival of early music in the twentieth century led to a number of large and small discoveries that significantly enriched the history of European music. Byzantine music became one of the new continents that appeared on the map of European musicology in the twentieth century. The process of comprehending the millennial history of Byzantine music as an important component of European musical culture, as a musical expression of Christian culture, as a tradition that had a powerful influence on the whole of Europe is far from been completed. The revival of the Ukrainian monodic church repertoire, that we observe today, is accompanied by an active search for historical information and appropriate vocal manners and style that lead to the Greek-Byzantine tradition. Comparative studies of Byzantine and East Slavic musical manuscripts have enormous heuristic potential and open up the opportunity to represent the thousand-year history of Ukrainian music, and not be limited to its modern period. The purpose of our work is to analyze the controversial concepts and approaches to understanding the Byzantine church chant tradition (“Byzantium after Byzantium”, in the words of Nicolae Iorga, traditionalism versus historicism); to show the prospects of Byzantine-Slavic musicological research and the need for its actualization in Ukraine; to present the educational course “Byzantine Music: Theory and Practice”. Methodological framework. The study is based on historicaltypological and comparative research methods. Results and scientific novelty of the work. The experience of comprehending the Byzantine church chant tradition as an important component of European musical culture was analyzed, discussion concepts and approaches in the development of musical Byzantinology of the twentieth century were highlighted. The prospects and relevance of Byzantine-Slavic music research were shown. The necessity of studying Byzantine music in musical institutions in modern Ukraine was substantiated, the current status of development of Ukrainian musical Byzantine studies was analyzed. An educational program on Byzantine music was presented, and the range of related scientific and methodological discussion topics was outlined.